2017
DOI: 10.1111/ejn.13565
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory evaluation in Mild Cognitive Impairment: correlation with neurocognitive performance and endothelial function

Abstract: Mild Cognitive Impairment (MCI) is an intermediate condition between normal aging and dementia, associated with an increased risk of progression into the latter within months or years. Olfactory impairment, a well-known biomarker for neurodegeneration, might be present in the condition early, possibly representing a signal for future pathological onset. Our study aimed at evaluating olfactory function in MCI and healthy controls in relation to neurocognitive performance and endothelial function. A total of 85 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 64 publications
0
9
0
Order By: Relevance
“…Our study further supports the previous literature that has developed the association between OD and cognitive dysfunction. 19,[36][37][38][39][40] This association continued to be present when controlling for potential demographic and comorbid factors, including concomitant GD, which represents a novel finding. Furthermore, our analyses revealed that cognitive dysfunction was associated with OD, regardless of the severity of dysfunction.…”
Section: Discussionmentioning
confidence: 73%
“…Our study further supports the previous literature that has developed the association between OD and cognitive dysfunction. 19,[36][37][38][39][40] This association continued to be present when controlling for potential demographic and comorbid factors, including concomitant GD, which represents a novel finding. Furthermore, our analyses revealed that cognitive dysfunction was associated with OD, regardless of the severity of dysfunction.…”
Section: Discussionmentioning
confidence: 73%
“…It is difficult to directly compare the magnitudes of associations in our investigation to those in previous studies, as the types of olfactory and cognitive assessments used in earlier studies differ substantially. Numbers (4‐40) and types of items utilized in odor identification testing has varied by study, and have included the University of Pennsylvania Smell Identification Test (UPSIT), the Sniffin’ Sticks Extended Test, and the Scandinavian Odor‐Identification Test . Neuropsychological tests used for assessment of cognitive functioning have been diverse, including the Modified Mini‐Mental State Examination, the Trail Making Test, the Short Test of Mental Status, and the Unified Parkinson's Disease Rating Scale, in addition to the tests used in this study—the DSST, the Animal Fluency Test, and the CERAD.…”
Section: Discussionmentioning
confidence: 87%
“…Our findings are consistent with earlier research, demonstrating a significant association of objectively measured smell impairment with increased risk of cognitive decline and dementia . It is difficult to directly compare the magnitudes of associations in our investigation to those in previous studies, as the types of olfactory and cognitive assessments used in earlier studies differ substantially.…”
Section: Discussionmentioning
confidence: 99%
“…Serby and colleagues (1996) found that first-degree relatives performed worse on a measure of odor identification when compared to a control group of community-dwelling older adults; further, the authors argued that impaired olfaction may be present before clinical symptoms. Similarly, two studies of participants with mild cognitive impairment (MCI), a known risk factor for AD, showed odor identification was impaired in people with MCI when compared to age- and gender-matched, cognitively normal controls, further adding to the evidence that suggests changes in the olfactory system may be useful in identifying those at risk for AD (Peters et al, 2003; Tonacci et al, 2017). These subsequent studies used similar methods to Serby et al (1996).…”
Section: Resultsmentioning
confidence: 98%